The Evaporation of Liquid Micro-Drops on the Heated Substrate; MATEC Web of Conferences; Vol. 92 : Thermophysical Basis of Energy Technologies (TBET-2016) - Semenov A. O. Andrey Olegovich (2017, 2017)
Title screen